Hybrid WDM/multibeam free-space optics for multigigabit access network - Al-Gailani, Samir A. (Kluwer Academic Publishers, 2015)
Hybrid wavelength division multiplexing/multibeam free-space optics (FSO) is a promising technique to overcome atmospheric attenuation due to tropical rain and to fulfill the growing demand for increased communication bandwidth and scalability. In this study, a hybrid four channel 1.25-Gb/s WDM/multibeam FSO network having four wavelengths with standard downlink channel spacing of 0.8 nm (100 GHz) is proposed. The hybrid WDM/multibeam FSO technique improved the performance of an FSO link in terms of the received power, link distance, data rate, and scalability. The proposed technique provided access data to four end users, each at a data rate of 1.25 Gb/s along an FSO link distance of 1,100 m